Era Keemasan Dinasti ‘Abbâsîyah: Analisis Perubahan Fungsional Francesca Cancian - Warsito, Loekisno Choiril (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article will basically discuss the development of the structural functional theory in particular that has been developed by Francesca Cancian, commonly known as the Functional Analysis of Change. The importance of using the analysis is because basically people development is often analogous to the process of evolution; a change into a form of ?perfection?. Thus, after a discussion of the theoretical propositions then it will be applied to the case of social and cultural change during the Abbasid dynasty, especially in the era of Caliph al-Ma?mûn?s leadership. It is found that social and cultural systems at the time of Abbasid dynasty were very dynamic and steady so that the golden age can be achieved.